Change dynamics and related leadership competencies - C. Von Eck; A. Verwey (SA Journal of Human Resource Management, 2007)
The purpose of this study was to develop a framework containing a set of leadership competencies required for major change types. It also compared the views of managers and employees on the importance of these competencies as well as the degree to which managers display the competencies. Ten leaders participated in the qualitative phase of the study and 60 managers and 74 employees responded to the survey. The major outcomes of the study included the competency framework as well as the competencies where statistically significant differences between the managers’ and employees’ views on, a) the degree to which the managers display the competencies as well as b) the importance assigned to the competencies, were found.